2013
DOI: 10.1016/j.jembe.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Resource use of two damselfishes, Stegastes planifrons and Stegastes adustus, on Guadeloupean reefs (Lesser Antilles): Inference from stomach content and stable isotope analysis

Abstract: International audienceStegastes planifrons and Stegastes adustus are two abundant territorial damselfishes of Caribbean coral reefs. Their trophic niches and their food utilisation on Guadeloupean reefs at two contrasting sites were compared on the basis of stomach content and stable isotope analyses (15N/14N and 13C/12C ratios). While ingested food items slightly differed between species, the assimilation of each food source (macroalgae, turf, benthic invertebrates and detritus) calculated with a concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…At the same time, the low palatability of Dictyota sp for herbivorous fishes was explained by its high content of deterrent molecules (Vallim et al 2005, Fong andPaul 2011). The high assimilation of fleshy macroalgae could also be linked to other macroalgae species, because fleshy macroalgae can have very close isotopic signatures at the same site (Dromard et al 2013). Previous studies demonstrated the important role of detritus in the diet of herbivorous fishes (Crossman et al 2001, Wilson et al 2003, Crossman et al 2005, Ferreira and Gonçalves 2006, Max et al 2013.…”
Section: Resource Use By Herbivorous Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the low palatability of Dictyota sp for herbivorous fishes was explained by its high content of deterrent molecules (Vallim et al 2005, Fong andPaul 2011). The high assimilation of fleshy macroalgae could also be linked to other macroalgae species, because fleshy macroalgae can have very close isotopic signatures at the same site (Dromard et al 2013). Previous studies demonstrated the important role of detritus in the diet of herbivorous fishes (Crossman et al 2001, Wilson et al 2003, Crossman et al 2005, Ferreira and Gonçalves 2006, Max et al 2013.…”
Section: Resource Use By Herbivorous Fishesmentioning
confidence: 99%
“…At the same time, the quality of food resources could explain their use by fishes (Montgomery and Gerking 1980;Dromard et al 2013). The nutritional quality of food sources can be evaluated by measuring the concentrations of proteins, lipids and carbohydrates in sources.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there were no significant relationships between benthic components and the Layman's metrics of the damselfish. The farming damselfish feed on their cultivated algae but also on the invertebrate communities and detritus that become established within the algal mat (Wilson and Bellwood, 1997;Dromard et al, 2013), suggesting two possible sources of variability; the invertebrate community and the algae. Recent studies have shown that in the Spermonde Archipelago there is significant variation in invertebrate recruitment in relation to distance from shore (Plass-Johnson et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of stable isotopes in coral reef food webs offers a powerful tool in elucidating trophic variation among consumers (Cocheret de la Moriniere et al, 2003;Carassou et al, 2008;Kolasinski et al, 2009;Greenwood et al, 2010;Dromard et al, 2013Dromard et al, , 2014Plass-Johnson et al, 2013, 2015b, however further clarification of sources of variability is needed to successfully apply this method within highly diverse systems. In our study, turf algae was more abundant at the degraded sites, however, the parrotfish C. bleekeri may have altered its feeding behavior because of specific structural (rubble) preferences for finding foods with 13 C values closer to Padina sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation